Chemistry Online Course: its Implementation for Preservice Chemistry Teachers’ Profile of Collaboration Skills and Communication Confidence - Erfan Priyambodo; Das Salirawati; Primastuti, Metridewi (Jurnal Zarah, 2025)
The development of sience, technology, and transformation in various sector allows the need of capable measure: how effective their role in learning interactions. This study seeks to reveal the profile of collaboration skills (CS) and communication confidence (CC) of pre-service chemsitry teacher (PCT). Convenience sampling technique was adopted for this study. A total of 26 PCTs were involved as research samples. The research intervention was conducted through six online lectures for PCT. Group discussions and presentations were implemented to collect data. Therefore, non-tests were used as data collection techniques. Data were obtained through two closed-ended questionnaires: the Collaborative Skill Questionnaire (CS-Q) and the Communication Confidence Questionnaire (CC-Q). The validity of the instruments was tested theoretically and empirically. Sixteen of the 20 CS-Q items and 22 of the 30 CC-Q items were valid. The Cronbach's alpha reliability estimates for the CS-Q and CC-Q instruments were 0.753 and 0.804, respectively. With data in the form of a Likert scale, descriptive statistics were used to analyze the profile levels of the PCT-CS and PCT-CC. The level criteria were divided into five categories. Based on these results, the PCT-CS was generally at a good level. Meanwhile, the PCT-CC level was sufficient. Based on the research results that have gone through the data analysis stage, learning activities need to implement methods that are capable of training PCT-CS and PCT-CC